UNDANG-UNDANG PEMELUKAN ISLAM DI MALAYSIA: Law on Conversion to Islam in Malaysia - Abu Bakar, Siti Adibah; Ismail, Siti Zubaidah (Jurnal Syariah, 2018)
In recent years, questions have been raised involving welfare and education of converts in Malaysia particularly on how they are managed by the religious authorities and whether there is sufficient resources to assist with their needs. The aim of this article is to study the existing legislation relating conversion into Islam in Malaysia. All states’ provisions are examined using descriptive method. It is found that specific provisions on conversion into Islam under the enactment of administration of religion of Islam are available though there are some differences on certain matters. Even so, the standard four main elements are registration procedures, obligations, rights of converts and the status of the children of converts. The study also found that even these matters were allocated in the state provisions, they are still insufficient to solve certain problems facing the converts. Some recommendations are highlighted to improve the management of the converts.